Competitiveness analysis and factors that influence the export of Indonesian shrimp commodities - Erlangga Agustino Landiyanto, Muryani, Dian Ratna Sari, (Opción, 2019)
The purpose of this study was to analyse the level of the country’s competitiveness in the shrimp market and the factors affecting the shrimp exports in major importing countries. The analysis was conducted through the application of Revealed Comparative Advantage (RCA) and Panel Gravity Model. The findings showed that the country’s GDP per capita and distance variables have a negative relationship with shrimp commodity exports while the GDP per capita for the importing countries, export prices, and population have a positive relationship. In conclusion, the Indonesian GDP and GDP in the destination country have a positive effect on the exports.